Associating GB characteristics with its sink efficiency in absorbing Frank loops in Cu. (February 2021) - Chen, J.; Dang, K.; Vo, H.T.; Hosemann, P.; Fensin, S.J.
Abstract: Molecular dynamics (MD) simulations are performed to investigate the interaction of a migrating grain boundary (GB) with interstitial Frank loops, using a set of GBs along the [100] tilt axis in Cu as model systems. Our results show that the interaction is directly related to the misorientation angle. Specifically, three modes of interaction are observed as a function of misorientation angle. The sink efficiency of a GB, namely, the capability of a GB to absorb the Frank loops, increases with misorientation angle. The above trends are explained based on the differences in the structural units comprising the GB. Additionally, the transition angle between different modes can be altered by varying the local GB structure. Graphical abstract: Image, graphical abstract